1996
DOI: 10.1074/jbc.271.2.901
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Transcription Factor Sp1 in Regulating the Expression of the WAF1/CIP1 Gene in U937 Leukemic Cells

Abstract: The Waf1/Cip1 protein induces cell cycle arrest through inhibition of the activity of cyclin-dependent kinases and proliferating cell nuclear antigen. Expression of the WAF1/CIP1 gene is induced in a p53-dependent manner in response to DNA damage but can also be induced in the absence of p53 by agents such as growth factors, phorbol esters, and okadaic acid. WAF1/CIP1 expression in U937 human leukemic cells is induced by both phorbol ester, a protein kinase C activator, and by okadaic acid, an inhibitor of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
183
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(205 citation statements)
references
References 28 publications
19
183
3
Order By: Relevance
“…Deletion of Spl-1 and Spl-2 from pWPdel-Bst XI to generate pWPlOl did not result in further reduction of the transcriptional activation (4.5-fold), suggesting that Spl-1 and Spl-2 within the p21 promoter was not essential for vinorelbine-mediated p21 activation. This effect is distinct from the effects of phorbol ester and of okadaic acid (Biggs et al, 1996). However, using the reporter pWPdel-Sma that contains Spl-5 and Spl-6, the expression only achieved approximately a two-fold induction (Po0.01).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Deletion of Spl-1 and Spl-2 from pWPdel-Bst XI to generate pWPlOl did not result in further reduction of the transcriptional activation (4.5-fold), suggesting that Spl-1 and Spl-2 within the p21 promoter was not essential for vinorelbine-mediated p21 activation. This effect is distinct from the effects of phorbol ester and of okadaic acid (Biggs et al, 1996). However, using the reporter pWPdel-Sma that contains Spl-5 and Spl-6, the expression only achieved approximately a two-fold induction (Po0.01).…”
Section: Discussionmentioning
confidence: 83%
“…Several important biological modifiers have been shown to activate p21 transcription through different Spl binding sites (Cartel and Tyner, 1999). For example, phorbol ester and okadaic acid induce p21 expression through Spl-1 and Spl-2 sites (Biggs et al, 1996), whereas the Spl-3 site in the promoter of p21 has been shown to be required for p21 induction by transforming growth factor-b, histone deacetylase inhibitors such as TSA and butyrate, lovastatin, nerve growth factor (NGF) as well as calcium (Datto et al, 1995;Nakano et al, 1997;Prowse et al, 1997;Sowa et al, 1997;Lee et al, 1998;Billon et al, 1999). In this report, we demonstrated that Spl-3 and Spl-4 in the promoter of human p21 gene are required for vinorelbinemediated transcriptional restoration of p21 in the p21-deficient Al cells, which may provide a new mechanism in drug-mediated p21 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides p53, transcription factor Ap-2 (Zeng et al, 1997), E2F-1/DP-1 complex (Hiyama et al, 1997), E2A (Prabhu et al, 1997), an ets-oncogene related E1AF (Funaoka et al, 1997), C/EBP , RAR (Liu et al, 1996a), VDR (Liu et al, 1996b), STATs (Chin et al, 1996), and Sp1 family (Biggs et al, 1996;Li et al, 1998;Owen et al, 1998;Prowse et al, 1997;Yan and Zi , 1997) are known to stimulate p21 promoter activity. Our results show that Ras induces p21 transcriptionally and that the Ras-responsive region in p21 promoter spans a short region downstream of the nucleotide 7110 relative to the transcription start site.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effect of p53 on p21 WAF1/CIP1 upregulation by DAC, we investigated the effect of DAC (1 mM), MS-275 (1 mM) and phorbol 12-myristate 13-acetate (PMA) (10 and 25 nM) on p21 WAF1/CIP1 expression in ML-1 cells (p53-WT) and HL-60 cells (p53-null) (Wolf and Rotter, 1985). PMA is a protein kinase C activator known to induce p21 WAF1/CIP1 in a p53-independent fashion (Biggs et al, 1996). As seen in Figure 5a, all three agents as well as TSA (300 nM) upregulated p21 WAF1/CIP1 within 48 h in the p53-WT ML-1 cells.…”
Section: Impact Of Sequential Administration Of Dnmt and Hdac Inhibitmentioning
confidence: 99%